Pengaruh Kualitas Produk, Harga, Promosi Dan Pelayanan Terhadap Kepuasan Konsumen Serta Dampaknya Pada Keputusan Pembelian - Marpaung, Budiman; Mekaniwati, Ani (LPPM Institut Bisnis dan Informatika Kesatuan, 2020)
This research aims to : a) determine the direct and simultaneous influence of production quality, price, promotion and service quality on customer satisfaction, b). kow the direct and simultaneous influence of production quality, price, promotion, service quality and customer satisfaction on purchasing decicions, c). determine the indirect and total impact on purchasing decicions through interventing variable customer satisfaction. The study was conducted on consumers of coffee processing machines. Respondents were determined by purposive sampling and accidental sampling. The numbers of respondents 79 people. The analysis method used is multiple linier regression with path analysis. The results showed : a) production quality and promotional activities have a direct and significant effect on positive direction on consumer satisfaction and purchasing decicions, while the quality of service the direct is not significant, but with a positive direction on customer satisfaction and buying decicions. b) price have a direct and significant effect with a negative direction on contumer satisfaction and consumer purchasing decicions, c) consumer satisfaction has a direct and significant effect on the positive direction of purchasing decicions, d) production quality, price, promotional activities and service quality simultaneously have a significant effect on contumer satisfaction, e) production quality, price, promotional activities, service quality and customer satisfaction simultaneously have a significant effect on purchasing decicions, f). consumer satisfaction as an interventing variable has an impact on increasing the total coefficient through increasing the indirect coefficient Keywords: production quality, price, promotion service, satisfaction, decicions